Metadichol® A Nano Lipid Emulsion that Expresses All 49 Nuclear Receptors in Stem and Somatic Cells - Raghavan, Palayakotai R. (Archives of Clinical and Biomedical Research, 2023)
Human nuclear receptors (NRs) involve 49 ligand-dependent transcription factors that are important for regulating the cell cycle and processes. There are many literature references on NR expression in many organs, abnormal cells, and tissues. However, a simple universal method to study the expression of NR is still missing. Here, we present systematic profiling of NRs in human umbilical cord stem cell lines and assess the expression of the 49 human NRs by quantitative real-time (qRT)-PCR using Metadichol, a nanoemulsion made of natural lipid alcohol. Metadicholtreated umbilical cord cells and fibroblasts, where all cells expressed NRs at a concentration range of 1 picogram per ml to 100 ng per ml in a dose dependent manner, were detected by qRT-PCR and qualified by Western blotting. This method will allow the study of many organs and tissues and expand our understanding of the role of NRs in mitigating diseases. Highlights: Metadichol treatment of somatic cells leads to all 49 nuclear receptors being expressed. Depending on the cell and concentration of Metadichol used, fold changes are different. The method could be used to study many cells and disease cells to better understand NR expression patterns and implications.The results suggest that Metadichol is a universal ligand to all nuclear receptors. Metadichol is controlling regulation of the expression of Nuclear receptors.